Etika Tasawuf Guru: Studi Pemikiran Imam al-Ghazali dan Syekh Muhammad Amin al-Kurdi - Akh Syaiful Rijal; Lutfi Hakim (TADRIS: Jurnal Pendidikan Islam, 2021)
This study aims: (1) to identify how the ethics of teacher Sufism according to Imam al-Ghazali and Sheikh Muhammad Amin al-Kurdi; and (2) To find out how the teacher's Sufism ethical thinking compared between the two. This research method includes the type of library research. The main data sources are the book Ihya 'Ulumiddin, Ayyuhal Walad by Imam al-Ghazali, and the book Tanwirul Qulub by Sheikh Muhammad Amin al-Kurdi. The analysis uses content analysis and comparison methods. As a result, the ethics of teachers from the Sufism perspective according to Imam al-Ghazali and Sheikh Muhammad Amin al-Kurdi are in the form of ethical-religious so that the ethics of teachers are more directed at the Sufism behavior of a mursyid to his students. Second, the similarity of the teacher’ ethic based on Sufism perspective according to Imam al-Ghazali and Sheikh Muhammad Amin al-Kurdi is that the teacher must be care to their students and know their students’ intellectual competence. The difference, Imam al-Ghazali recommends that the teachers guide their students to be real human through an exemplary approach. Meanwhile, Sheikh Muhammad Amin al-Kurdi also emphasized compassion in interacting with students, but in internalizing values it ​​uses a verbal approach, namely giving advice.